Urgensi Penetapan Hutan Adat Bagi Masyarakat Kampung Adat Cireundeu Ditinjau Menurut Hak-Hak Konstitusional dalam UUD NRI 1945 - Muhammad Raihan Nurhakim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Indonesia possesses vast forest areas with great potential. On the other hand, before the establishment of the Indonesian state, indigenous communities already exercised control over forests in the Indonesian territory based on customary rights. Therefore, the existence and customary rights of indigenous communities over forests are recognized in the Constitution. However, in reality, there are still many indigenous communities that their rights to the forests they have managed for generations have not been fully acknowledged, one of them is Cireundeu indigenous community. The lack of recognition causes these communities to face issues related to their customary rights over the forests.In fact, the 1945 Constitution of the Republic of Indonesia actually guarantees the rights of indigenous peoples regarding their forest. One way to realize that rights is by declarating customary forests for the indigenous communities of Cireundeu. This research examines the importance of the declaration of customary forests for the Cireundeu Indigenous Community in light of the rights of indigenous communities guaranteed by the Constitution. This research is a normative legal study. The approaches used are the statutory approach and the conceptual approach. The results of this research indicate that the declaration of customary forests for the indigenous communities of Cireundeu is crucial to ensure their constitutional rights to be recognized and respected, along with their traditional rights, to achieve well-being, particularly in terms of food security, to protect their cultural identity, and to safeguard a healthy and sustainable environment.